Planejar em Desenhos: a visão das professoras de Educação Infantil - Mucheroni, Alice Meirelles (2026)
This research investigated the use of drawing as a resource for pedagogical planning in Early Childhood Education, seeking to answer the central question: what is the teachers’ view of the action of planning through drawings? The scarcity of studies that relate drawing and planning reinforced the relevance of the investigation. The theoretical foundation of the research leads us to understand the drawing of planning as an ethical and aesthetic act, in which the teacher is constituted in a dialogical relationship with the other, assuming their uniqueness and responsibility toward the world. This perspective is articulated with Participatory Pedagogies, which value the child as protagonist and the listening of their multiple languages. In this context, drawing takes a place in sensitive planning, conceived as a flexible, documentary, and expressive pathway. The study also dialogues with the idea of the Reflective Teacher, which leads us to reflect on drawing as a tool for reflection in action and the transformation of practice, and with Visual Literacy, which legitimizes drawing as an essential competence for thinking, organizing, and communicating pedagogical ideas. The data were produced in five meetings held at a Municipal Center for Early Childhood Education in São Carlos, with the participation of eleven teachers. As instruments, we obtained the drawings produced by the teachers, written records, the researcher’s reflective journal, conversation circles, and word clouds, which were analyzed using Discursive Textual Analysis (DTA). The results initially showed insecurity and resistance among the teachers to drawing, resulting from the predominance of writing in pedagogical practice. However, throughout the meetings, drawing was re-signified as a resource that favored clarity, organization, and playfulness in planning. The participants recognized that drawing made it possible to get closer to their own pedagogical intentions, as well as to broaden reflection on the spaces, times, and materials of Early Childhood Education. We conclude that drawing can be incorporated into planning as a complementary language, enriching the process of pedagogical organization and strengthening child-centered practices. The research contributed to the professional development of the teachers and resulted in an educational product composed of suggestions for integrating drawing into teaching planning.